The examination of vegetable- and mineral oil-based inks' effects on print quality: Green printing effects with different oils - AYDEMİR, CEM; ARMAN KANDIRMAZ, EMİNE; YENİDOĞAN, SEMİHA (SAGE PUBLICATIONS LTD, 2018)
Introduction: Printing inks oil selection is related to the desired nature of the varnish in the ink production. Petroleumderived mineral oils and vegetable oils can be used in offset inks. Methods: In this study, the behaviors of vegetable- and mineral oil-based inks on uncoated and coated paper surfaces were investigated in terms of printability. Solid tone test prints were done with offset printing of these inks. Print gloss of the printed samples was measured and a light fastness test was implemented on these samples in order to determine the resistance to fading. Absorption behavior and contact angles of the ink-printed films on the test papers were measured with the sessile water drop method depending on time, and surface energies were calculated. Results: On both paper types, linseed-soybean oil-based vegetable ink gave the highest brightness value. The lowest print gloss results on the paper were obtained from soybean oil-based inks. The lowest color change was recorded with mineral oil-based inks on gloss-coated papers. According to the ink-film-surface relation, when the contact angle is high, surface energy decreases and the absorbency of the ink-film is lower. Conclusions: In this study, the behaviors of vegetable- and mineral oil-based inks on different paper surfaces, and the effect on the quality of printability as well as differences, have been evaluated, taking environmental and health factors into consideration.
Keywords: Absorption; contact angle; printability; soy-based ink; vegetable oil ink; volatile organic compound; PAPER; WATER